Literature Review: Pemanfaatan Instrumentasi Tes Minat terhadap Layanan Bimbingan dan Konseling - Rahmiati Aulia Sukma; Savana Putri Sofyan; Gladys Chandra Dipuri; Qotrun Maulina; Kinanti Kesuma Dewi; Lulu Sofia Ansori (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Interest and aptitude tests help in recognizing children's potential early on, so that parents and educators can plan education that is more suitable and supports the optimal development of children's potential. The purpose of this study is to help individuals know that interest and aptitude test instrumentation has a major impact in directing individuals in developing themselves, both in academics and careers. Children who study and work according to their interests tend to be more motivated, happy and accomplished. With a clear understanding of interests and aptitudes, children can make better decisions regarding future education, major and career choices. In this study we used the Literature Review method by collecting several sources. The results and discussion of the literature review discussion regarding interest tests, interest inventories, and Android-based psychological test applications in guidance and counseling in schools show that these tools are very important to help students determine educational and career paths according to their interests and talents. Interest tests help reduce uncertainty in career decision-making, improve the fit between individuals and jobs or study programs, and expand understanding of the psychological tendencies underlying their choices.